2014
DOI: 10.4081/ija.2014.569
|View full text |Cite
|
Sign up to set email alerts
|

Assessing food production capacity of farms in periurban areas

Abstract: The assessment of food production capacity is particularly important in small-and medium-sized cities, which have greater chances to develop local periurban farming. To date the literature has been focused on niche sectors of the food market, such as alternative food networks and public procurement for school canteens, but less attention has been paid to urban food production. We present a method to assess the food production capacity in periurban areas, which we tested on meat production (beef and lamb) in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 23 publications
0
16
0
2
Order By: Relevance
“…In this context, we investigated the ability of peri-urban farms to feed the local population. Filippini et al (2014) highlighted that the potential food capacity depends not only on the effective size and number of farms but also on the collective actions targeting a product. The analysis of the beef and lamb production from peri-urban farms and sold in the local food supply chain showed that most local beef production was sold locally under a local label, whereas most of the locally produced lamb, which is not labelled, was marketed through conventional food chains.…”
Section: Food Issue Links Agriculture and The Citymentioning
confidence: 99%
“…In this context, we investigated the ability of peri-urban farms to feed the local population. Filippini et al (2014) highlighted that the potential food capacity depends not only on the effective size and number of farms but also on the collective actions targeting a product. The analysis of the beef and lamb production from peri-urban farms and sold in the local food supply chain showed that most local beef production was sold locally under a local label, whereas most of the locally produced lamb, which is not labelled, was marketed through conventional food chains.…”
Section: Food Issue Links Agriculture and The Citymentioning
confidence: 99%
“…These multifunctional activities of peri-urban agriculture enrich both the rural and the urban context [19,20].…”
Section: Multifunctional Sustainable and Peri-urban Agricultural Symentioning
confidence: 99%
“…As already described by Filippini et al (2014), this region has a surface of 500 km 2 and consists of six municipalities located in the coastal plain of the Arno river and on the hilly area known as the Monte Pisano (917 m a.s.l). The area has a population density of almost 400 inhabitants per km 2 and follows the European urban demographic trend for the last decade: a decrease in the city-centre inhabitants (-4% in the last decade) and a significant increase in the periurban areas (+8% in the last decade).…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaire was based on the main characteristics of the farm, the crop management, the marketing of the products, the farmer projects and the main advantages and disadvantages of being near an urban centre. For more details, see Filippini et al (2014).…”
Section: Data Collectionmentioning
confidence: 99%